Digital Transformation In Human Resource Management: Challenges And Opportunities - Sri Utami Nurhasanah; Jenris Mangatur Sinambela (Brilliant International Journal Of Management And Tourism, 2022)
The integration of digital technologies into Human Resource Management (HRM) practices has become imperative in the contemporary organizational landscape. This paper explores the challenges and opportunities arising from the digital transformation in HRM. It synthesizes existing literature and empirical studies to elucidate the multifaceted nature of this transformation. Challenges include resistance to change, privacy concerns, and skill gaps among HR professionals. Conversely, digitalization offers opportunities for enhancing recruitment processes, employee engagement, and performance management. Additionally, it enables the adoption of data-driven decision-making and facilitates remote work arrangements. The paper underscores the need for organizations to navigate these challenges effectively while leveraging digital technologies to optimize HRM processes. By embracing digital transformation strategically, organizations can harness its potential to foster agility, innovation, and competitive advantage in the dynamic contemporary business environment